2011
DOI: 10.1162/jocn.2010.21521
|View full text |Cite
|
Sign up to set email alerts
|

Sound Processing Hierarchy within Human Auditory Cortex

Abstract: Both attention and masking sounds can alter auditory neural processes and affect auditory signal perception. In the present study, we investigated the complex effects of auditory-focused attention and the signal-to-noise ratio of sound stimuli on three different auditory evoked field components (auditory steady-state response, N1m, and sustained field) by means of magnetoencephalography. The results indicate that the auditory steady-state response originating in primary auditory cortex reflects the signal-to-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Frontal cir-cuitry, by contrast, is thought to support more flexible learning on the basis of updated predictions, including those involved in reversals (9,25,47). We note also that the auditory P2m and the N1m (plus EEG analogs of these components) have been associated in the past with modulation by cognitive factors such as attention (32,48), thought to arise due to influences from frontal cortex (32), whereas the P1m is typically found to be less influenced by putatively frontal influences such as attention (33).…”
Section: Discussionmentioning
confidence: 69%
“…Frontal cir-cuitry, by contrast, is thought to support more flexible learning on the basis of updated predictions, including those involved in reversals (9,25,47). We note also that the auditory P2m and the N1m (plus EEG analogs of these components) have been associated in the past with modulation by cognitive factors such as attention (32,48), thought to arise due to influences from frontal cortex (32), whereas the P1m is typically found to be less influenced by putatively frontal influences such as attention (33).…”
Section: Discussionmentioning
confidence: 69%
“…MEG studies have shown that selectively listening to sound embedded in a complex auditory scene modulates longer latency (∼100-250 ms) responses in association auditory cortex but not the shorter latency (∼50 ms) steady-state response in core auditory cortex (21,34,35), as is also the case for MEG/EEG responses to transient sounds (13,(36)(37)(38). PET studies also indicate that the areas posterior to core auditory cortex are more activated when speech is interfered by temporally modulated noise than stationary noise (39,40), because modulated noise contains speech-like features and requires additional processes of information selection.…”
Section: Discussionmentioning
confidence: 99%
“…Source locations and orientations (one dipole for each hemisphere) were estimated for each subject and each run (preconditioning/postconditioning) individually. The estimated sources were fixed in location and orientation and served as a spatial filter during the calculation of the source strength for each affective condition (Okamoto et al, 2011). We calculated a repeated-measures ANOVA on the source strengths for each condition, using the factors session, valence, and hemisphere in the N1m time interval.…”
Section: Ermf Recordings and Analysismentioning
confidence: 99%